Effects of Manila clam Ruditapes philippinarum culture on the macrobenthic community - Hou, Wenhao; Wei, Xiangtao; Bai, Weihao; Zheng, Yajuan; Tan, Qiyin; Liu, Zhaojun; Rong, Bowen; Ge, Changzi (Frontiers in Marine Science, 2023)
Macrobenthic bioturbation affects the environment, and variances in habitat, such as decreased dissolved oxygen concentration and increased ammonia concentration, affects the macrobenthic community. The relationship between macrobenthos and habitat factors may be a mutually causal relationship. The bottom-sowing culture for Manila clam Ruditapes philippinarum in many coastal countries plays an important role in coastal fisheries, and the relationship between Manila clam and other macrobenthos affects the ecological stability of the bottom-sowing culture zone. It is necessary to explore the relationship between them to manage the waters used for the bottom-sowing culture for Manila clam. In this study , from June to October 2021, the field investigation on macrobenthos including Manila clam and their habitat factors, such as particle size, nutrient content, redox potential, and organic matter content, in 21 experimental communities enclosed by bolting-silk net in Shuangdao Bay, Weihai, Shandong, China was conducted, during which macrobenthos functional groups were determined by feed sources and motor behavior. The results showed that Manila clam biomass was 7.215±0.984 g/m2 (calculated by dry soft tissue weight), and it was positively correlated with the biomass of macrobebthos functional groups B1, G1 and P1; water content in sediment; sulfide content in interstitial water; the Shanon-Wiener diversity index; Pielou’s evenness index and the W statistic of the ABC (Abundance-Biomass Comparison) curve (p< 0.05). Moreover, it was negatively correlated with sediment particulate size and HCl-NO3 content in sediment (p< 0.05). The action of Manila clam to habitats was the dominant role of the interaction between clam and habitat. Thus, the bottom-sowing culture for Manila clam does not decrease the macrobenthic community stability, and the invasion of other macrobenthos into the bottom-sowing culture zones for Manila clam may be accidental or inevitable. The results of our study suggest that the management of the bottom-sowing culture for Manila clam should be conducted from ecosystem level; i.e., fishing and aquaculture in the same waters are regarded as two components of an ecosystem; manage them together, rather than treat them separately.